Peningkatan Motivasi Belajar Siswa Menggunakan Model Problem Based Learning Berbantuan Media Quizizz di Kelas III SDN 7 Cakranegara Tahun Pelajaran 2022/2023 - Swari, Ni Ketut Indah; Yati, Mega Suci; Khair, Baiq Niswatul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Learning activities carried out in the classroom greatly determine the quality of learning that takes place. Based on the results of observations made, it was found that the learning that took place was not student-centered and learning activities were still carried out conventionally. This causes low learning motivation for class III students at SDN 7 Cakranegara. The research carried out aims to improve learning regarding this problem by implementing the Problem Based Learning learning model assisted by Quizizz media. Quizizz is used as a learning medium and learning evaluation tool. This type of research is Classroom Action Research which takes place in 2 cycles. Data collection techniques are carried out through observation and documentation. The Classroom Action Research model used is the Kemmis and Mc model. Taggart. The subjects of this research were class III students at SDN 7 Cakranegara for the 2022/2023 academic year with a total of 26 students consisting of 9 female students and 17 male students. The results of this research are that in the pre-cycle and cycle 1 stages, the average student was in the fairly good learning motivation criteria with a percentage of 61% and 63%, while in cycle 2 there was an increase in student learning motivation, namely the average student was in the good criteria with a percentage 76%. Based on the results of this research, it can be concluded that the application of the Problem Based Learning learning model assisted by Quizizz media can increase students' learning motivation.